Method for preparing high-performance skutterudite compound through composite modification of carbon quantum dots
By combining carbon quantum dots with CoSb3-based cobalt ore thermoelectric materials, and using rapid ultrasonic composite and SPS sintering processes, the limitations of improving the thermoelectric performance of CoSb3-based cobalt ore thermoelectric materials in the existing technology are solved, and efficient thermoelectric performance improvement and waste recycling are achieved.
Patent Information
- Application Number
- CN202410185376.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-02-19
AI Technical Summary
The existing CoSb3-based cobalt ore thermoelectric materials have limitations in improving thermoelectric performance, and traditional doping, filling and composite metal nanophase methods are difficult to improve performance infinitely.
Carbon quantum dots are used as the second phase to recombinate the thermoelectric material of CoSb3-based cobalt ore. Through rapid ultrasonic composite and SPS sintering processes, uniform dispersion and efficient combination of carbon quantum dots are achieved.
The thermoelectric properties of thermoelectric materials are significantly improved, including enhanced Seebeck coefficient, reduced thermal conductivity and improved power factor, while solving the problems of agricultural and industrial waste treatment and realizing the recycling of resources.
Smart Images

Figure CN119630256A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of thermoelectric materials, and in particular to a method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots. Background Art
[0002] Thermoelectric materials are environmentally friendly and highly efficient clean energy materials. Based on the Seebeck and Peltier effects, thermoelectric materials can realize the mutual conversion of thermal energy and electrical energy, and can generate electricity and refrigerate low-grade heat sources such as natural temperature differences and waste heat from thermal power plants. Due to the potential thermoelectric applications of cobalt compounds, such as harvesting heat generated in industrial processes and automobile operations, and alternative refrigeration that avoids the use of environmentally harmful gases, they have attracted widespread interest. Binary cobalt is a body-centered cubic structured compound with a general chemical formula of MX3 (M represents a transition metal element, such as Co, Fe, Rh or Ir; X represents a phosphorus element, such as P, As or Sb, and its space group is Im3. At present, the thermoelectric properties of cobalt are mainly improved by doping, filling, nano-sizing or nano-composite cobalt.
[0003] The size and mass of the doped metal atoms are different from those of the framework atoms, which causes local lattice distortion in the skutterudite and increases point defects, thereby scattering phonons, ultimately achieving the purpose of reducing the lattice thermal conductivity of the material and improving the thermoelectric figure of merit. However, it is precisely because the replaced atoms Te, Se, etc., have certain differences in size, electronegativity, and atomic mass from the framework atoms that they cannot be replaced infinitely; each skutterudite unit cell contains two large vacancies (i.e., icosahedral vacancies of Sb). Due to its special structural characteristics, some metal atoms (such as Na, Ba, Yb, Ce, In, etc.) or non-metal atoms (such as S, Se, I, Cl, Br, etc.) can be filled in, which have a strong scattering effect on phonons in the lattice, thereby reducing the thermal conductivity and lattice thermal conductivity of the material, and can show the conduction characteristics of phonon glass-electron crystal (PGEC). The nano- or nano-composite nature of thermoelectric materials is now a major new direction for further improving their thermoelectric performance. Nanomaterials have significantly different physical properties from bulk materials. When the size of the material reaches the nanoscale, the density of electronic states changes greatly. With nano-scaling and reducing the dimensionality of the material, it is possible that α, σ and κ can change independently, so optimizing a certain parameter can improve the thermoelectric performance of the material. In addition, compared with the scattering of carriers, the high-density grain boundaries caused by nanomaterials have stronger selective scattering of phonons, which can greatly reduce the thermal conductivity κ of the material. Compounding a small amount of nano second phase can greatly enhance the scattering effect of phonons, greatly reduce the thermal conductivity of thermoelectric materials, and increase the Seekbeck coefficient, while the electrical conductivity is only slightly reduced, thereby significantly improving the thermoelectric performance index of the compound.
[0004] Therefore, it is necessary to provide a new method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots to solve the above technical problems. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots, which breaks the traditional method of improving thermoelectric performance of existing CoSb3-based skutterudite thermoelectric materials, such as doping, filling and composite metal nanophases. Recently, organic and organic-inorganic thermoelectric materials have gradually attracted people's interest and received widespread attention. Compared with traditional TE materials, carbon-based materials generally show high flexibility, fracture toughness, high strength and high temperature stability. Carbon has a variety of allotropes because it can hybridize in sp, sp2, sp3 bonds, which enables it to form zero-dimensional (such as fullerene), one-dimensional (such as carbon nanotubes), two-dimensional (such as graphene) and three-dimensional (such as diamond) structures, and is therefore one of the most widely used elements in the periodic table. In addition, carbon is one of the most abundant elements on earth (ranked 15th among all elements), and most of its allotropes are non-toxic and lightweight. Carbon nanomaterials as second-phase composite metal-based thermoelectric materials can serve as electron transport channels and improve electrical conductivity. The addition of carbon nanotubes can also reduce the carrier concentration, thereby increasing the Seebeck coefficient, which usually leads to a significant increase in the power factor. At the same time, the scattering of phonons is enhanced, the thermal conductivity is significantly reduced, and the thermoelectric properties of thermoelectric materials are greatly improved. At present, there are many second-phase composites of carbon nanomaterials, such as carbon nanotubes and graphene. Compared with the 3D form of the same material, low-dimensional structures can carry higher ZT. Quantum dots (QDs) can be regarded as quasi-zero-dimensional structures. Due to the stronger quantum confinement in these maximum confinement structures, their state density can have σ-like spikes. These sharp peaks are predicted to be the best electronic structure for TE performance, especially to enhance the Seekbeck coefficient. In addition, strong boundary scattering in quantum dots can also greatly reduce thermal conductivity, even below the value of alloys. In fact, quantum dots of various materials (including carbon quantum dots) have been found or predicted to have excellent TE properties.
[0006] Carbon quantum dots (CDs) are a quasi-zero-dimensional carbon-based material with a size of less than 10nm. As a new type of carbon-based nanomaterial, it has attracted extensive research interest for many years due to its rich physical and chemical properties, good biocompatibility, unique optical properties, low cost, low toxicity, eco-affinity, rich functional groups (such as amino, hydroxyl, carboxyl), high stability and electron mobility since its discovery. The main advantages of carbon dots are that they can be easily prepared from various carbon-based materials, low price, environmental friendliness, and in line with the development trend of sustainable materials. Carbon quantum dots are widely used in many fields such as medical imaging technology, environmental monitoring, chemical analysis, catalyst preparation, and energy development. They have shown great potential and have extremely broad application prospects. Carbon quantum dots have broad prospects and space as the second phase of thermoelectric composites.
[0007] Moreover, carbon quantum dots can use a variety of heteroatoms (nitrogen, sulfur, phosphorus, boron, fluorine, etc.) and metals (Zn, Mg, Ag, Au, Cu, Ga, etc.) as dopants to improve the physical and chemical properties of CDs. Compared with commonly used heteroatoms, metals are better electron donors, with more unoccupied orbitals outside and larger atomic radii. Therefore, after metal ions are doped into CDS, compared with heteroatom doping, the chance of changing the charge density and charge transfer form between the graphene matrix and the metal ions will be greater, thereby improving the physical and chemical properties of CDs to a greater extent. The introduction of metal ions can change the electronic structure of CDs, affect the spin density and charge distribution of CDs, and then increase the number of catalytic active centers in CDs. Compared with undoped CDs, metal ion-doped CDs also show better catalytic performance. In addition, the introduction of metal ions also improves the conductivity and electron donation and acceptance capabilities of CDS, thereby promoting the electron transfer process. Metal doping such as Zn, Mn, and Gd helps the radiative recombination of electrons and holes on the surface of CDs.
[0008] In order to solve the above technical problems, the method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots provided by the present invention comprises the following steps: Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0009] Yb, Te, Co, Sb single substance powders are used as raw materials and weighed according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; the materials weighed according to the proportion are added with grinding aid acetone or ethanol for sufficient grinding and mixing, and then placed in a vacuum drying oven for drying; after the grinding aid is completely volatilized, the powder is cold-pressed into a shape by a tablet press, the cold-pressed block sample is sealed inside a quartz tube and then vacuumized, the vacuum quartz tube is placed in a ceramic dry pot, green silicon carbide is placed inside the dry pot as a microwave auxiliary absorber, asbestos is placed around the crucible as a heat-insulating material with a thickness of 50 to 100 mm, the quartz tube and the crucible are placed in a microwave oven for microwave synthesis, the synthesized sample is crushed and then ground to obtain CoSb3-based skutterudite;
[0010] Step 2: Preparation of carbon quantum dots
[0011] Soybean meal carbon quantum dots: Pour crushed soybean meal and deionized water into a beaker, the mass ratio of soybean meal to deionized water is 1:20, ultrasonically mix and put into a microwave digester for microwave hydrothermal synthesis. The synthetic product is centrifuged at high speed to obtain a yellow-brown supernatant, which is then dialyzed, rotary evaporated, and freeze-dried to finally obtain solid soybean meal carbon quantum dots;
[0012] Metal-based carbon quantum dots: crushed industrial sludge is used as the metal-based carbon source, and a certain amount of aqueous solution of Ce(NO3)3, Yb(NO3)3, Eu(NO3)3, etc. is added as a metal dopant, and the mass ratio of the carbon source to the aqueous solution is 1:5; ultrasonic mixing is placed in a microwave digester for microwave hydrothermal synthesis, and the synthetic product is obtained by high-speed centrifugation to obtain a yellow-brown supernatant, which is then dialyzed using a dialysis bag and vacuum dried to finally obtain solid metal-based carbon quantum dots;
[0013] Step 3: Rapid ultrasonic compounding and SPS sintering
[0014] A certain amount of prepared carbon dots is dissolved in deionized water, ethanol or acetone, and crushed CoSb3-based skutterudite is added for ultrasonic vibration. After ultrasonic vibration, the composite material is centrifuged and vacuum dried, and then the carbon dot-composite skutterudite is subjected to spark plasma sintering (SPS sintering) to obtain a carbon quantum dot-composite skutterudite thermoelectric composite material.
[0015] The preparation process of the present invention can be used to prepare a large amount of carbon quantum dots from agricultural waste soybean meal, which not only solves the problems of large output, difficult treatment, and environmental pollution of agricultural and forestry waste, but also develops a recycling technology for agricultural and forestry waste; the preparation process of the present method can be used to prepare a composite pure carbon quantum dot CoSb3-based thermoelectric material with high thermoelectric performance, and effectively improve the purity and density of the obtained thermoelectric material; the preparation process of the present method can be used to prepare metal-based carbon dots by using industrial sludge as a carbon source, and compound them into CoSb3-based cobaltite thermoelectric materials to further improve their thermoelectric performance and mechanical properties, while providing a new direction for the problem of industrial sludge treatment, thereby achieving the purpose of utilizing waste resources and protecting the environment.
[0016] Preferably, the pressure of the cold pressing molding in step 1 is 6 to 9 MPa.
[0017] Preferably, in step 1, the vacuum degree in the quartz tube is ensured to be above 10-3 MPa.
[0018] Preferably, the power of the microwave synthesis in step 1 is 500-1000 W, and the heating time is 5-20 min.
[0019] Preferably, the CoSb3-based skutterudite block synthesized by microwave in the step 1 is ground into powder with a mesh size of less than 200.
[0020] Preferably, in the step 2, the soybean meal and industrial sludge raw materials must be further crushed to less than 60 meshes.
[0021] Preferably, in step 2, the microwave hydrothermal temperature is 180-240° C., and the reaction time is 6-12 h.
[0022] Preferably, in step 2, Ce(NO3)3·6H2O, Yb(NO3)3·5H2O, and Eu(NO3)3·6H2O are respectively prepared into aqueous solutions with a concentration of 5 to 30 mM.
[0023] Preferably, the rotation speed of the high-speed centrifugation in step 2 is 8000-16000 r / min, the centrifugation time is 10-20 min, and it is repeated three times.
[0024] Preferably, in step 2, a 500-2000Da dialysis bag is used and the dialysis is performed for 10-48 hours, and the freeze-drying is performed for 30-70 hours.
[0025] Preferably, in step 2, the purity of Ce(NO3)3·6H2O, Yb(NO3)3·5H2O and Eu(NO3)3·6H2O in step 2 is 99.99%.
[0026] Preferably, according to the mass percentage, the carbon quantum dots in step three are ultrasonically compounded with skutterudite at a ratio of 0.05-0.3%, 0.5-1%, 1-3%, 3-5%, and 5-20%.
[0027] Preferably, in step three, the ultrasonic oscillation time is 10 to 30 min, the centrifugal speed is 4000 to 12000 r / min, the vacuum drying is 4 to 8 h, and the drying temperature is 55 to 70°C.
[0028] Preferably, in step three, the SPS sintering temperature is 580-650° C., the pressure is 40-60 MPa, and the holding time is 10-15 min.
[0029] Preferably, the purity of the raw material Co powder and Te powder is 99.99%, and the purity of the raw material Sb powder and Yb powder is 99.9%.
[0030] Compared with the related art, the method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots provided by the present invention has the following beneficial effects:
[0031] (1) The method of preparing a high-performance skutterudite compound by composite modification of carbon quantum dots of the present invention takes advantage of the characteristics that carbon quantum dots are easily soluble in water or organic solvents and can be evenly dispersed, and uses a method of rapid ultrasonic oscillation of a carbon dot solution to composite the carbon quantum dots into a CoSb3-based skutterudite thermoelectric material, so that the carbon quantum dots can quickly enter the mesoporous system of the CoSb3-based skutterudite, so that the carbon quantum dots are evenly dispersed into the CoSb3-based skutterudite thermoelectric material, achieving a uniform composite effect. Finally, the CoSb3-based skutterudite thermoelectric material is prepared by combining SPS sintering. While achieving the requirements of rapid and uniform composite, the purpose of simplifying the composite process and optimizing the process is achieved, and a CoSb3-based skutterudite thermoelectric composite material with good thermoelectric performance can be obtained.
[0032] (2) The method of preparing high-performance skutterudite compounds by composite modification of carbon quantum dots of the present invention can easily obtain the carbon source of carbon nanomaterials by using agricultural (industrial) waste such as soybean meal and industrial sludge as carbon sources to prepare carbon quantum dots, thereby realizing simple, economical and green synthesis of carbon nanomaterials. In addition, the method solves the problems of large output, difficult treatment and environmental pollution of agricultural (industrial) waste, and develops a recycling technology for agricultural (industrial) waste. Agricultural (industrial) waste as carbon source has become a new field for green synthesis of carbon quantum dots with its extensive economic advantages.
[0033] (3) A method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots of the present invention, preparing quasi-zero-dimensional biomass carbon quantum dots with a size less than 10nm, with a large number of electrons, holes and rich physical and chemical properties on its surface, good biocompatibility, unique optical properties, low cost, low toxicity, ecological affinity, rich functional groups (such as amino, hydroxyl, carboxyl), high stability and electron mobility, etc. As the second phase composite CoSb3-based skutterudite thermoelectric material, carbon quantum dots can be used as electron transmission channels, improve electrical conductivity, and appropriately reduce carrier concentration, thereby improving Seebeck coefficient, which usually leads to a significant increase in power factor. At the same time, it also enhances the scattering of phonons, significantly reduces thermal conductivity, and greatly improves the thermoelectric performance of thermoelectric materials.
[0034] (4) The method of preparing high-performance skutterudite compounds by composite modification of carbon quantum dots of the present invention further prepares metal-based carbon quantum dots. Metals are better electron donors, have more unoccupied orbits on their exterior, and have larger atomic radii. Therefore, after metal ions are doped into CDs, compared with heteroatom doping, the chances of changing the charge density and charge transfer form between the graphene matrix and the metal ions will be greater, thereby improving the physicochemical properties of CDs to a greater extent. The introduction of metal ions can change the electronic structure of CDs, affect the spin density and charge distribution of CDs, improve the electrical conductivity of CDs and the ability to donate and accept electrons, thereby promoting the electron transfer process and facilitating the radiation recombination of electrons and holes on the surface of CDs. By compounding metal-based carbon quantum dots into CoSb3-based skutterudite thermoelectric materials, their thermoelectric properties can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the XRD pattern of the skutterudite composite carbon dot thermoelectric material prepared by the present invention;
[0036] Figure 2 This is a transmission electron microscope image of the carbon dots prepared by the present invention;
[0037] Figure 3 This is a power factor diagram of the skutterudite bulk thermoelectric material prepared in the present invention. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.
[0039] Please refer to Figure 1 , Figure 2 and Figure 3 ;
[0040] Example 1
[0041] A method for preparing a high-performance skutterudite compound by composite modification of carbon quantum dots comprises the following steps:
[0042] Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0043] Take Yb, Te, Co, Sb single substance powder as raw materials, weigh 10g according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; add grinding aid acetone or ethanol to fully grind and mix for 30min, and put it into a 60℃ vacuum drying oven for drying; after the grinding aid is completely volatilized, press the powder to 9MPa by a tablet press to cold press the powder, seal the cold pressed block sample in a vacuum quartz tube, and place it in a 900W microwave oven for microwave synthesis heating time of 10min, crush the synthesized sample and grind it below 200 mesh to obtain CoSb3-based skutterudite;
[0044] Step 2: Preparation of carbon quantum dots
[0045] 20 ml of a mixture of soybean meal and deionized water was poured into a beaker, wherein the mass ratio of soybean meal to deionized water in the mixture was 1:20. The mixture was ultrasonically mixed and placed in a microwave digester for microwave hydrothermal synthesis at 180°C for 8 hours. The synthesized product was centrifuged at 10,000 r / min for 12 minutes to obtain a yellow-brown supernatant, which was then placed in a 500Da dialysis bag for 12 hours, and excess water was evaporated by rotary evaporation. The mixture was freeze-dried at -80°C for 50 hours to finally obtain carbon quantum dots with high purity.
[0046] Step 3: Rapid ultrasonic compounding and SPS sintering
[0047] The carbon quantum dots in step 2 are weighed and dissolved in deionized water, and CoSb3-based skutterudite is added and mixed. According to the mass percentage, the ratio of CoSb3-based skutterudite to carbon quantum dots is 99.95%:0.05%; the mixed material is ultrasonically vibrated for 30 minutes, the composite material is centrifuged after ultrasound, the supernatant is removed, and vacuum dried at 55°C for 4 hours, and then the carbon dot-composite skutterudite is spark plasma sintered (SPS sintering) at a sintering temperature of 650°C, a pressure of 50MPa, and a holding time of 10 minutes to obtain a carbon quantum dot-composite skutterudite thermoelectric composite material.
[0048] Example 2
[0049] A method for preparing a high-performance skutterudite compound by composite modification of carbon quantum dots comprises the following steps:
[0050] Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0051] Take Yb, Te, Co, Sb single substance powder as raw materials, weigh 10g according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; add grinding aid acetone or ethanol to fully grind and mix for 30min, and put it into a 60℃ vacuum drying oven for drying; after the grinding aid is completely volatilized, press the powder to 9MPa by a tablet press to cold press the powder, seal the cold pressed block sample in a vacuum quartz tube, and place it in a 900W microwave oven for microwave synthesis heating time of 10min, crush the synthesized sample and grind it below 200 mesh to obtain CoSb3-based skutterudite;
[0052] Step 2: Preparation of carbon quantum dots
[0053] 20 ml of a mixture of soybean meal and deionized water was poured into a beaker, wherein the mass ratio of soybean meal to deionized water in the mixture was 1:20. The mixture was ultrasonically mixed and placed in a microwave digester for microwave hydrothermal synthesis at 220°C for 10 hours. The synthesized product was centrifuged at 10000 r / min for 12 minutes to obtain a yellow-brown supernatant, which was then placed in a 500Da dialysis bag for 24 hours, and excess water was evaporated by rotary evaporation. The mixture was freeze-dried at -80°C for 50 hours to finally obtain carbon quantum dots with high purity.
[0054] Step 3: Rapid ultrasonic compounding and SPS sintering
[0055] The carbon quantum dots in step 2 are weighed and dissolved in deionized water, and CoSb3-based skutterudite is added and mixed. According to the mass percentage, the ratio of CoSb3-based skutterudite to carbon quantum dots is 99.5%:0.5%; the material mixture is ultrasonically shaken for 30 minutes, and the composite material is centrifuged after ultrasound, the supernatant is removed, and vacuum dried at 55°C for 4 hours, and then the carbon dot-composite skutterudite is spark plasma sintered (SPS sintering) at a sintering temperature of 650°C, a pressure of 50MPa, and a holding time of 10 minutes to obtain a carbon quantum dot-composite skutterudite thermoelectric composite material.
[0056] Example 3
[0057] A method for preparing a high-performance skutterudite compound by composite modification of carbon quantum dots comprises the following steps:
[0058] Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0059] Take Yb, Te, Co, Sb single substance powder as raw materials, weigh 10g according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; add grinding aid acetone or ethanol to fully grind and mix for 30min, and put it into a 60℃ vacuum drying oven for drying; after the grinding aid is completely volatilized, press the powder to 9MPa by a tablet press to cold press the powder, seal the cold pressed block sample in a vacuum quartz tube, and place it in a 900W microwave oven for microwave synthesis heating time of 10min, crush the synthesized sample and grind it below 200 mesh to obtain CoSb3-based skutterudite;
[0060] Step 2: Preparation of metal-based carbon quantum dots
[0061] 20 ml of the mixture of sludge and deionized water was poured into a beaker, the mass ratio of sludge to deionized water in the mixture was 1:20, the mixture was ultrasonically mixed and placed in a microwave digester for microwave hydrothermal synthesis at 220°C for 12 hours, the synthetic product was centrifuged at 10000 r / min for 12 minutes to obtain a yellow-brown supernatant, which was placed in a 500Da dialysis bag for 12 hours, and vacuum dried at 55°C for 5 hours to finally obtain heterometallic carbon quantum dots with high purity;
[0062] Step 3: Rapid ultrasonic compounding and SPS sintering
[0063] The carbon quantum dots in step 2 are weighed and dissolved in deionized water, and CoSb3-based skutterudite is added and mixed. According to the mass percentage, the ratio of CoSb3-based skutterudite to carbon quantum dots is 99%:1%. After the materials are mixed, ultrasonic vibration is performed for 30 minutes, and the composite material is centrifuged after ultrasound, the supernatant is removed, and vacuum dried at 55°C for 4 hours, and then the carbon dot composite skutterudite is subjected to spark plasma sintering (SPS sintering) at a sintering temperature of 650°C, a pressure of 50MPa, and a holding time of 10 minutes to obtain a carbon quantum dot composite skutterudite thermoelectric composite material.
[0064] Example 4
[0065] A method for preparing a high-performance skutterudite compound by composite modification of carbon quantum dots comprises the following steps:
[0066] Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0067] Take Yb, Te, Co, Sb single substance powder as raw materials, weigh 10g according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; add grinding aid acetone or ethanol to fully grind and mix for 30min, and put it into a 60℃ vacuum drying oven for drying; after the grinding aid is completely volatilized, press the powder to 9MPa by a tablet press to cold press the powder, seal the cold pressed block sample in a vacuum quartz tube, and place it in a 900W microwave oven for microwave synthesis heating time of 10min, crush the synthesized sample and grind it below 200 mesh to obtain CoSb3-based skutterudite;
[0068] Step 2: Preparation of Ytterbium-based Carbon Quantum Dots
[0069] 20 ml of the mixture of sludge and deionized water was poured into a beaker, the mass ratio of sludge to deionized water in the mixture was 1:20, and then 1 ml of 10 mM Yb(NO3)3 solution was added, and the mixture was ultrasonically mixed and placed in a microwave digester for microwave hydrothermal synthesis at 220°C for 12 hours. The synthetic product was centrifuged at 10000 r / min for 12 minutes to obtain a yellow-brown supernatant, which was placed in a 500Da dialysis bag for dialyzation for 24 hours, and vacuum dried at 55°C for 5 hours to finally obtain ytterbium-based carbon quantum dots with high purity;
[0070] Step 3: Rapid ultrasonic compounding and SPS sintering
[0071] The carbon quantum dots in step 2 are weighed and dissolved in deionized water, and CoSb3-based skutterudite is added and mixed. According to the mass percentage, the ratio of CoSb3-based skutterudite to carbon quantum dots is 97%:3%; after the materials are mixed, ultrasonic vibration is performed for 30 minutes, and the composite material is centrifuged after ultrasound, the supernatant is removed, and vacuum dried at 55°C for 4 hours, and then the carbon dot composite skutterudite is subjected to spark plasma sintering (SPS sintering) at a sintering temperature of 650°C, a pressure of 50MPa, and a holding time of 10 minutes to obtain a carbon quantum dot composite skutterudite thermoelectric composite material.
[0072] Example 5
[0073] A method for preparing a high-performance skutterudite compound by composite modification of carbon quantum dots comprises the following steps:
[0074] Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0075] Take Yb, Te, Co, Sb single substance powder as raw materials, weigh 10g according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; add grinding aid acetone or ethanol to fully grind and mix for 30min, and put it into a 60℃ vacuum drying oven for drying; after the grinding aid is completely volatilized, press the powder to 9MPa by a tablet press to cold press the powder, seal the cold pressed block sample in a vacuum quartz tube, and place it in a 900W microwave oven for microwave synthesis heating time of 10min, crush the synthesized sample and grind it below 200 mesh to obtain CoSb3-based skutterudite;
[0076] Step 2: Preparation of Europium-based Carbon Quantum Dots
[0077] 20 ml of the mixture of sludge and deionized water was poured into a beaker, the mass ratio of sludge to deionized water in the mixture was 1:20, and then 5 ml of 10 mM Eu(NO3)3 solution was added, and the mixture was ultrasonically mixed and placed in a microwave digester for microwave hydrothermal synthesis at 220°C for 12 hours. The synthesized product was centrifuged at 10000 r / min for 12 minutes to obtain a yellow-brown supernatant, which was placed in a 500Da dialysis bag for dialyzation for 24 hours, and then vacuum dried at 55°C for 5 hours to finally obtain europium-based carbon quantum dots with high purity;
[0078] Step 3: Rapid ultrasonic compounding and SPS sintering
[0079] The carbon quantum dots in step 2 are weighed and dissolved in deionized water, and CoSb3-based skutterudite is added and mixed. According to the mass percentage, the ratio of CoSb3-based skutterudite to carbon quantum dots is 95%:5%; after the materials are mixed, ultrasonic vibration is performed for 30 minutes, and the composite material is centrifuged after ultrasound, the supernatant is removed, and vacuum dried at 55°C for 4 hours, and then the carbon dot composite skutterudite is subjected to spark plasma sintering (SPS sintering) at a sintering temperature of 650°C, a pressure of 50MPa, and a holding time of 10 minutes to obtain a carbon quantum dot composite skutterudite thermoelectric composite material.
[0080] Example 6
[0081] A method for preparing a high-performance skutterudite compound by composite modification of carbon quantum dots comprises the following steps:
[0082] Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials
[0083] Take Yb, Te, Co, Sb single substance powder as raw materials, weigh 10g according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; add grinding aid acetone or ethanol to fully grind and mix for 30min, and put it into a 60℃ vacuum drying oven for drying; after the grinding aid is completely volatilized, press the powder to 9MPa by a tablet press to cold press the powder, seal the cold pressed block sample in a vacuum quartz tube, and place it in a 900W microwave oven for microwave synthesis heating time of 10min, crush the synthesized sample and grind it below 200 mesh to obtain CoSb3-based skutterudite;
[0084] Step 2: Preparation of Cerium-based Carbon Quantum Dots
[0085] 20 ml of the mixture of sludge and deionized water was poured into a beaker, the mass ratio of sludge to deionized water in the mixture was 1:20, and then 10 ml of 10 mM Ce(NO3)3 solution was added, and the mixture was ultrasonically mixed and placed in a microwave digester for microwave hydrothermal synthesis at 220°C for 12 hours. The synthesized product was centrifuged at 10000 r / min for 12 minutes to obtain a yellow-brown supernatant, which was placed in a 500Da dialysis bag for dialyzation for 24 hours, and vacuum dried at 55°C for 5 hours to finally obtain cerium-based carbon quantum dots with high purity;
[0086] Step 3: Rapid ultrasonic compounding and SPS sintering
[0087] Weigh the carbon quantum dots in step 2 and dissolve them in deionized water, and add CoSb3-based skutterudite to mix. According to the mass percentage, the ratio of CoSb3-based skutterudite to carbon quantum dots is 90%:10%; after the materials are mixed, ultrasonic vibration is carried out for 30 minutes, and the composite material is centrifuged after ultrasound, the supernatant is removed, and vacuum dried at 55°C for 4 hours, and then the carbon dot composite skutterudite is subjected to spark plasma sintering (SPS sintering) at a sintering temperature of 650°C, a pressure of 50MPa, and a holding time of 10 minutes to obtain a carbon quantum dot composite skutterudite thermoelectric composite material.
[0088] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots, characterized in that: The following steps are involved: Step 1: Preparation of CoSb3-based skutterudite thermoelectric materials Yb, Te, Co, Sb single substance powders are used as raw materials and weighed according to the following mass ratio: Yb: Co: Sb: Te = 0.4: 4: 11.8: 0.2; the materials weighed according to the proportion are added with grinding aid acetone or ethanol for sufficient grinding and mixing, and then placed in a vacuum drying oven for drying; after the grinding aid is completely volatilized, the powder is cold-pressed into a shape by a tablet press, the cold-pressed block sample is sealed inside a quartz tube and then vacuumized, the vacuum quartz tube is placed in a ceramic dry pot, green silicon carbide is placed inside the dry pot as a microwave auxiliary absorber, asbestos is placed around the crucible as a heat-insulating material with a thickness of 50 to 100 mm, the quartz tube and the crucible are placed in a microwave oven for microwave synthesis, the synthesized sample is crushed and then ground to obtain CoSb3-based skutterudite; Step 2: Preparation of carbon quantum dots Soybean meal carbon quantum dots: Pour crushed soybean meal and deionized water into a beaker, the mass ratio of soybean meal to deionized water is 1:20, ultrasonically mix and put into a microwave digester for microwave hydrothermal synthesis. The synthetic product is centrifuged at high speed to obtain a yellow-brown supernatant, which is then dialyzed, rotary evaporated, and freeze-dried to finally obtain solid soybean meal carbon quantum dots; Metal-based carbon quantum dots: crushed industrial sludge is used as the metal-based carbon source, and a certain amount of aqueous solution of Ce(NO3)3, Yb(NO3)3, Eu(NO3)3, etc. is added as a metal dopant, and the mass ratio of the carbon source to the aqueous solution is 1:5; ultrasonic mixing is placed in a microwave digester for microwave hydrothermal synthesis, and the synthetic product is obtained by high-speed centrifugation to obtain a yellow-brown supernatant, which is then dialyzed using a dialysis bag and vacuum dried to finally obtain solid metal-based carbon quantum dots; Step 3: Rapid ultrasonic compounding and SPS sintering A certain amount of prepared carbon dots is dissolved in deionized water, ethanol or acetone, and crushed CoSb3-based skutterudite is added for ultrasonic vibration. After ultrasonic vibration, the composite material is centrifuged and vacuum dried, and then the carbon dot-composite skutterudite is subjected to spark plasma sintering (SPS sintering) to obtain a carbon quantum dot-composite skutterudite thermoelectric composite material.
2. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: The pressure of the cold pressing in step 1 is 6-9 MPa.
3. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 1, the vacuum degree in the quartz tube is ensured to be above 10-3 MPa.
4. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: The power of the microwave synthesis in the step 1 is 500-1000W, and the heating time is 5-20min.
5. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: The CoSb3-based skutterudite block synthesized by microwave in the step 1 is ground into powder with a mesh size of less than 200.
6. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 2, the soybean meal and industrial sludge raw materials must be further crushed to less than 60 meshes.
7. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 2, the microwave hydrothermal temperature is 180-240° C., and the reaction time is 6-12 hours.
8. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 2, Ce(NO3)3·6H2O, Yb(NO3)3·5H2O, and Eu(NO3)3·6H2O are respectively prepared into aqueous solutions with a concentration of 5 to 30 mM.
9. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: The rotation speed of high-speed centrifugation in step 2 is 8000-16000 r / min, the centrifugation time is 10-20 min, and it is repeated three times.
10. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 2, a 500-2000Da dialysis bag is used for dialysis for 10-48 hours, and freeze-dried for 30-70 hours.
11. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 2, the purity of Ce(NO3)3·6H2O, Yb(NO3)3·5H2O and Eu(NO3)3·6H2O is 99.99%.
12. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: According to the mass percentage, in the step three, the carbon quantum dots are ultrasonically compounded with skutterudite at a ratio of 0.05-0.3%, 0.5-1%, 1-3%, 3-5%, and 5-20%.
13. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 3, the ultrasonic oscillation time is 10 to 30 minutes, the centrifugal speed is 4000 to 12000 r / min, the vacuum drying is 4 to 8 hours, and the drying temperature is 55 to 70°C.
14. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: In the step 3, the SPS sintering temperature is 580-650° C., the pressure is 40-60 MPa, and the holding time is 10-15 min.
15. The method for preparing high-performance skutterudite compounds by composite modification of carbon quantum dots according to claim 1, characterized in that: The purity of the raw material Co powder and Te powder is 99.99%, and the purity of the raw material Sb powder and Yb powder is 99.9%.
Citation Information
Patent Citations
Graphene compounded with stibine cobalt base skutterudite thermoelectric material and preparation method of material
CN102931335A
Method for preparing high-performance square cobalt ore by combining two steps of microwave rapid heating and mechanical alloying
CN109371282A
Thermoelectric powder and materials with improved thermostability and manufacturing methods thereof
KR1020170024467A
Skutterudite thermoelectric materials of hole-compensated type and method of making the same
WO2013009430A1